Characterization of thin coatings based on ZnO for photonic applications - Suarez, Gustavo (2019)
We present a comparison between zinc oxide films made by sol-gel dip-coating and spray-pyrolysis to be employed in optoelectronic applications. Grain size, shape, roughness, thickness, band gap, composition, crystalline orientation, electrical resistivity, and optical guided modes were evaluated by AFM, SEM, EDS, optical transmittance, electrical resistance, and end-fire coupling method, respectively. From these results, it was determined that dip-coated film is thinner (with a thickness of about 130 nm) than the spray-pyrolysis one (of about 500 nm), whereas the former showed lower roughness and higher electrical resistivity. Furthermore, a 532 nm continuous laser was coupled across the sprayed film because of its greater thickness. We conclude that the studied techniques can be complementarily implemented to obtain high-performance coatings for photonic applications, combining the lower roughness of dip coating and the wider thickness of spray-pyrolysis films.